2013
DOI: 10.1002/ajh.23466
|View full text |Cite
|
Sign up to set email alerts
|

Short telomere length is associated with NOTCH1/SF3B1/TP53 aberrations and poor outcome in newly diagnosed chronic lymphocytic leukemia patients

Abstract: Most previous studies on telomere length (TL) in chronic lymphocytic leukemia (CLL) are based on referral cohorts including a high proportion of aggressive cases. Here, the impact of TL was analyzed in a population-based cohort of newly diagnosed CLL (n 5 265) and in relation to other prognostic markers. Short telomeres were particularly associated with high-risk genetic markers, such as NOTCH1, SF3B1, or TP53 aberrations, and predicted a short time to treatment (TTT) and overall survival (OS) (both P < 0.0001… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
32
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 28 publications
9
32
0
1
Order By: Relevance
“…Conversely, CLL cases with long TL were characterized by deletion 13q14, no cytogenetic alterations or only one abnormality. In agreement with our findings, a similar correlation between TL and the number of genomic aberrations was previously reported [12,17], supporting dysfunctional telomeres may be a key event driving genomic instability in tumors and correlate with the emergence of increased genomic complexity [25].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Conversely, CLL cases with long TL were characterized by deletion 13q14, no cytogenetic alterations or only one abnormality. In agreement with our findings, a similar correlation between TL and the number of genomic aberrations was previously reported [12,17], supporting dysfunctional telomeres may be a key event driving genomic instability in tumors and correlate with the emergence of increased genomic complexity [25].…”
Section: Discussionsupporting
confidence: 93%
“…Our results in CLL support a role for telomere shortening at the origin of genomic instability [24] and reinforce previous reports showing the adverse prognostic value of chromosome alterations in this pathology [6,8,29]. In this line, Mansouri et al [17] found that an increased number of large copy number aberrations as detected by high resolution SNP-arrays correlated with decreasing TL in CLL patients. Rossi et al [16] showed that short telomeres are an independent predictor of Richter's syndrome transformation, process associated to increased genetic complexity.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Mean inter-assay CV for relative telomere length was 4-8% 35 . Telomere/single copy gene values were calculated by 2 -ΔCt methodology.…”
Section: Telomere Lengthmentioning
confidence: 95%
“…The short telomeres were significantly associated with both reduced TTFT (medians 18 vs. 42 months for long telomeres; P=0.039) ( Figure 3A) and overall survival (OS) (medians 88 months vs. not reached for long telomeres; P=0.016) ( Figure 3B) in subset #2. Although a previous report showed relatively stable TL after treatment in CLL patients, 15 we cannot fully exclude an impact of therapy administration on survival analysis since a proportion of samples (24%) was collected after therapy. Regarding genetic defects, we also assessed their impact on OS.…”
Section: P=0039mentioning
confidence: 99%